A comparative study of the concept of public good in the political thought of Imam Khomeini and Ayatollah Naeini - abdola pirozi; Abdolhossein Allah karam; Ahmad Bakhshayeshi Ardestani; Aliakbar Amini (توسعه اجتماعی, 2021)
Common good as one of the basic concepts in political thought has not been studied independently yet. This concept, along with concepts such as public interests, public expediencies, public policy, common interests and common good, has formed the basis and foundation of most approaches and controversies of different schools. In the common discourse of political science, the public good refers to the material, cultural or institutional possibilities in which the members of a society share interests. This study aimed at providing the most fundamental sharing and differentiating aspects of Imam Khomeini and Ayatollah Naeini’s political ideas and their political views on the foundations of the theory of public good through a comparative study of their political ideas in the framework of the crisis theory of Thomas Spriggens. Accordingly, the main commonalities are the concepts such as legalism, denial of tyranny, the centrality of the role of the people in government and the differences, the form of government, the basis of government legitimacy and the conditions of Islamic rule. In general, both thinkers, according to scientific proposals in the field of the relationship between Sharia and politics, offered a special interpretation and created a new perspective in Shiite jurisprudential theories in dealing with new political concepts. Allameh Naeini's most central political views as the initiator of this movement in the Shiite political jurisprudential tradition were the rejection of tyranny and the jurisprudential justification of the constitutional government, which was based on his negative approach. On the other hand, Imam Khomeini, as the successor of Allama Naini, in this movement, with a broad and comprehensive approach and based on a positive approach, developed this issue.